HUBUNGAN KEPEMIMPINAN DAN PENGAWASAN TERHADAP KEDISIPLINAN KERJA PADA PT SUPEREX RAYA TANGERANG - Hardani Hardani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The research’s aim is to analyze the relationship between the leadership and the supervision toward the discipline of the employees in PT Superex Raya Tangerang. About 700 employees and selected randomly as the population of this research and for amount of 250 respondences as the sample of this research. The researcher used Statistical Package For Social Science (SPSS 17) to find out the relationship between the leadership and the supervision toward the discipline of the employees in PT Superex Raya Tangerang. The result of the study shows that there is a significant relationship between the leadership and the supervision toward the discipline of the employees in PT Superex Raya Tangerang. It shows that good leadership and good supervision increase the discipline among the employees.